Constructive side-channel analysis and secure design : 4th International Workshop, COSADE 2013, Paris, France, March 6-8, 2013, Revised Selected Papers - Prouff, Emmanuel (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th International Workshop, COSADE 2013, held in Paris, France, in March 2013. The 13 revised full papers presented together with two invited talks were carefully selected from 39 submissions and collect truly existing results in cryptographic engineering, from concepts to artifacts, from software to hardware, from attack to countermeasure.